2015
DOI: 10.14444/2054
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy-guided pedicle screw accuracy with a mini-open approach: a tomographic evaluation of 470 screws in 125 patients

Abstract: Our study demonstrated a high accuracy (90.2%) for 2-D fluoroscopy-guided pedicle screw using electromonitoring. Only 0.71% of the 470 screws had a major breach. Knowing the radiological spine pedicle anatomy and the correct interpretation of EMG are the key factors for this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Fourteen suitable articles were found and included. 3,6,18,[20][21][22][33][34][35]37,38,41,43,44 Data from Ryang et al, 34 Kantelhardt et al, 20 and Bydon et al 6 were identified as outliers. Table 5 summarizes the meta-analysis of screw revision rates from the included studies.…”
Section: Figmentioning
confidence: 99%
“…Fourteen suitable articles were found and included. 3,6,18,[20][21][22][33][34][35]37,38,41,43,44 Data from Ryang et al, 34 Kantelhardt et al, 20 and Bydon et al 6 were identified as outliers. Table 5 summarizes the meta-analysis of screw revision rates from the included studies.…”
Section: Figmentioning
confidence: 99%
“…22 Other modifications in the pedicle insertion technique such as the assistance of fluoroscopic view of the pedicle axis have been attempted and reported to improve the accuracy of the screw placement and reduce the risk of complications. [23][24][25][26] With the advent of technology, computer simulation software have been developed, which can also be used for training and practice. 27…”
Section: Discussionmentioning
confidence: 99%